High Emissions of Carbon Dioxide and Methane From the Coastal Baltic Sea at the End of a Summer Heat Wave - Humborg, Christoph; Geibel, Marc. C.; Sun, Xiaole; McCrackin, Michelle; Mörth, Carl-Magnus; Stranne, Christian; Jakobsson, Martin; Gustafsson, Bo; Sokolov, Alexander; Norkko, Alf; Norkko, Joanna (Frontiers in Marine Science, 2019)
The summer heat wave in 2018 led to the highest recorded water temperatures since 1926 – up to 21 C – in bottom coastal waters of the Baltic Sea, with implications for the respiration patterns in these shallow coastal systems. We applied cavity ring-down spectrometer measurements to continuously monitor carbon dioxide (CO2) and methane (CH4) surface-water concentrations, covering the coastal archipelagos of Sweden and Finland and the open and deeper parts of the Northern Baltic Proper. This allowed us to i) follow an upwelling event near the Swedish coast leading to elevated CO2 and moderate CH4 outgassing, and ii) to estimate CH4 sources and fluxes along the coast by investigating water column inventories and air-sea fluxes during a storm and an associated downwelling event. At the end of the heat wave, before the storm event, we found elevated CO2 (1583 µatm) and CH4 (70 nmol/L) concentrations. During the storm, a massive CO2 sea-air flux of up to 274 mmol m-2 d-1 was observed. While water-column CO2 concentrations were depleted during several hours of the storm, CH4 concentrations remained elevated. Overall, we found a positive relationship between CO2 and CH4 wind-driven sea-air fluxes, however, the highest CH4 fluxes were observed at low winds whereas highest CO2 fluxes were during peak winds, suggesting different sources and processes controlling their fluxes besides wind. We applied a box-model approach to estimate the CH4 supply needed to sustain these elevated CH4 concentrations and the results suggest a large source flux of CH4 to the water column of 2.5 mmol m-2 d-1. These results are qualitatively supported by acoustic observations of vigorous and widespread outgassing from the sediments, with flares that could be traced throughout the water column penetrating the pycnocline and reaching the sea surface. The results suggest that the heat wave triggered CO2 and CH4 fluxes in the coastal zones that are comparable with maximum emission rates found in other hot spots, such as boreal and arctic lakes and wetlands. Further, the results suggest that heat waves are as important for CO2 and CH4 sea-air fluxes as the ice break up in spring.